2022
DOI: 10.1002/pc.26983
|View full text |Cite
|
Sign up to set email alerts
|

Low‐velocity impact damage and compression after impact behavior of CF/PEEK thermoplastic composite laminates

Abstract: Impact resistance and damage tolerance are of great significance in the design of composite structures. This study researched the damage and failure mechanism of carbon fiber reinforced poly-ether-ether-ketone (CF/PEEK) composite laminates under the low-velocity impact (LVI) and compression after impact (CAI) loading conditions. The test included four impact energy levels (15, 30, 45, and 60 J) and compared the effect of two different stacking sequences ([0 /90 ] 8S and [0 /45 /90 /À45 ] 4S ) on performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…For the specimens SS1 and SS2 used in this study, the experimentally measured S u are 381 and 441 MPa, respectively. 37 As shown in Figure 10B, a higher impact energy resulted in a lower normalized residual strength, and it can be observed that the rate of decline slowed down. The increase ratio of normalized residual strength for SS1-IAH and SS2-IAH specimens, which were subjected to various energy levels, ranges from 22.1% to 31%.…”
Section: Compression Behaviormentioning
confidence: 82%
“…For the specimens SS1 and SS2 used in this study, the experimentally measured S u are 381 and 441 MPa, respectively. 37 As shown in Figure 10B, a higher impact energy resulted in a lower normalized residual strength, and it can be observed that the rate of decline slowed down. The increase ratio of normalized residual strength for SS1-IAH and SS2-IAH specimens, which were subjected to various energy levels, ranges from 22.1% to 31%.…”
Section: Compression Behaviormentioning
confidence: 82%
“…They also emphasized that TR‐CFRP has less delamination than R‐CFRP. Liu et al [ 36 ] investigated the damage and failure mechanisms of carbon fiber reinforced poly‐ether‐ether‐ketone (CF/PEEK) composite laminates subjected to LVI and CAI loading. Simulating the LVI and CAI properties of composite laminates, they developed a three‐dimensional finite element model based on continuous damage mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, regarding various types of composite laminates, many studies have been carried out to illuminate the impact damage mechanism as well as the deep negative effect of the LVI on the subsequent mechanical properties such as tensile test, [10] shearing, [11,12] bending [13][14][15][16] and compressive test. [17][18][19] The part of existing latest related research and their research contents are summarized and the first point to note is that even a tiny impact energy can lead to a significant decrease in the strength under various kinds of post-impact tests. In addition, the effect of LVI load on the post-impact behavior depends on a combination of multiple factors, such as original materials, the configuration of the specimens, and even size, and so forth.…”
Section: Introductionmentioning
confidence: 99%